Analisis Kinerja Keuangan Berdasarkan Rasio Likuiditas dan Solvabilitas Pada PT. Bank Muamalat Indonesia Tbk - Karlina, Honi; Idwal, Idwal; Afrianty, Nonie (Disclosure: Journal of Accounting and Finance, 2024)
Financial performance is an analysis that is carried out to see to what extent a company has implemented and applied the rules of financial enforcement properly and correctly. By measuring financial performance, it can be seen the prospects of growth and development of the company. A company is said to be successful when it has achieved a certain set performance. The purpose of this research is to find out the financial performance based on the ratio of liquidity and solvency in the PT. Bank Muamalat Indonesia Tbk period 2018-2022. This type of research is descriptive research with a quantitative approach. The sample in this study is the annual financial report of Bank Muamalat for the period 2018-2022. Data collection techniques are documentation and library with data analysis using miscrosof exel software. The research results show the financial performance of PT. Bank Muamalat Indonesia based on the liquidity ratio for the 2018-2022 period is in the unhealthy category. This can be seen from the quick ratio indicator in 2018-2020 in the unhealthy category but in 2021 and 2022 the healthy category, the cash ratio value in the unhealthy category, the loan to deposit ratio in the unhealthy category, the assets to loan ratio in the healthy category in accordance with Bank regulations Indonesia. Financial performance of PT. Bank Muamalat Indonesia based on its solvency ratio for the 2018-2022 period is in the healthy category. This can be seen from the Primary Ratio indicator in the healthy category. The secondary risk ratio indicator is in the unhealthy category. The capital ratio indicator is in the healthy category in accordance with Bank Indonesia regulations